Compatible operations in some subvarieties of the variety of weak Heyting algebras - San Martín, Hernán Javier (2013)
Weak Heyting algebras are a natural generalization of Heyting algebras (see [2], [5]). In this work we study certain subvarieties of the variety of weak Heyting algebras in order to extend some known results about compatible functions in Heyting algebras.